THE EFFECT OF MOTHERS’ AGE, SEX AND WEIGHT OF THE CHILD IN PREDICTING CAESAREAN DELIVERY AMONG WOMEN - Adah*†, V.; Achimugu*, D. (International Journal of Mathematical Analysis and Modelling, 2023)
Labor in child bearing is the onset of regular contractions and cervical change. The study aimed at investigating the probability of normal delivery given the sex, weight of Child and Age of mother. This research work covers the record of babies delivered in the Federal Medical Center Makurdi between the months of June to September 2016. Data was collected from the delivery register of the maternity ward/Labor room. The study employed the logistic regression to determine the probability of caesarean section among women given the Sex and Weight of the baby, and Age of the mother. The study revealed that factors such as the sex of child, weight of child, and age of the mother fits the model with p-values: 0.39089, 0.00422, and 0.00739 respectively, with the weight of the child and age of the mother are significant in predicting caesarean delivery. The likelihood ratio test shows that the fitted model adequately fits the data. In conclusion pregnant mothers should avoid foods that increases baby’s weight and aged pregnant mothers should attend antenatal regularly so they could be given the necessary medical attention.